Analisis Wacana Kritis terhadap Tagline “Indonesia Gelap” dalam Berita Detik.com - Naswa Dwi Putri Nasution; Najwa Naila; Siti Fadilla Siagian; Syairal Fahmy Dalimunthe (MUKASI: Jurnal Ilmu Komunikasi, 2025)
This study employs Critical Discourse Analysis (CDA) based on Theo van Leeuwen's model to examine the representation of social actors in Detik.com's news article titled "Muzani soal Demo 'Indonesia Gelap': Yang Prabowo Lakukan Timbulkan Kekagetan". The research focuses on the discursive strategies of exclusion (omission of actors) and inclusion (foregrounding of actors) to reveal how media framing shapes public perception of political events. Using a qualitative descriptive method, the analysis highlights three key findings: (1) The exclusion of demonstrators' voices and contextual background marginalizes their agency, reducing the event to a mere "surprise" narrative; (2) The dominant inclusion of Muzani's perspective positions him as an authoritative narrator, reinforcing a top-down interpretation of the protest; and (3) The portrayal of society as passive reactors (e.g., "kaget") rather than active participants reflects a power imbalance in media representation. The study underscores how Detik.com's linguistic choices—such as sensationalist diction ("kekagetan") and selective sourcing—construct a crisis-oriented discourse that aligns with elite political interests. These findings align with van Leeuwen's theory that media discourse reproduces social inequalities by privileging certain actors while silencing others. The research contributes to media literacy advocacy by revealing the ideological implications of news framing and calls for critical public engagement with online journalism.